Green Tourism Marketing Model1 - Ali Hasan (Media Wisata, 2015)
Green Tourism Marketing Model research as efforts to develop environmentally-friendly tourism destination, the synergy of government, business and community participation become the driving force of tourism product development with highly competitive.In the long term, this research aims to provide the marketing concept of green tourism as economic development effort and strengthen the environment (eco-growth) through the development of green tourism marketing models. The object of this research is achieved by (1) mapping a superior product green tourism; (2) generating a model of the development of green tourism marketing; (3) applying a model of development of green tourism marketing by groups of the local communities of the tourism business, (4) developing a model of green tourism marketing with quality function development (5) building green tourism areas; (6) involving the government to formulate laws/policies about tourist area of green zones and patterns of tourism business development for local communities which are optimal in economic development based on environmental sustainability (integrated eco-growth green tourism); (7) international publications in the journal of hospitality and tourism research (powered by Scopus) and (8) a draft of the green tourism marketing textbook. The methods of the research were conducted by (1) theoretical analysis of mapping superior product of green tourism; (2) identification of issues based on data in the field; (3) the development of green tourism models with test instruments; (4) achieving experiments in a limited test model, (5) the improvement of models and instruments; (6) implementation of the model (7) foster the spirit and commitment to building small business tourism (8) the establishment of the concept of the green tourism area. Therefore, the starting point of this research is the development of green tourism marketing models in developing this area of green tourism that can encourage the growth of tourism businesses that have the capability to create a multiplier effect for the improvement of employment opportunities and increase opportunities of tourism community welfare. The mix methods of quantitative and qualitative used in the research are achieved by three stages; stages of development and design, the pilot phase in a limited scope and validation phase in the form of an experimental analysis of the most effective to encourage the existence of green tourism marketing models into an embryo of a growing area of superior products of green tourism which are needed to integrate the development of tourism industry based on environment for both economic sustainability, social and cultural community and environmental resources itself.